2021
DOI: 10.1093/europace/euab256
|View full text |Cite
|
Sign up to set email alerts
|

The evidence for the implantable loop recorder in patients with inherited arrhythmia syndromes: a review of the literature

Abstract: Risk stratification of patients with inherited arrhythmia syndromes (IASs) can be challenging. Recent guidelines acknowledge a place for considering the implantable loop recorder (ILR) to outrule malignant arrhythmia as a cause of syncope in certain inherited arrhythmia patients who are at low risk of sudden cardiac death. In this comprehensive literature review, we evaluate the available evidence for the use of the ILR in the IASs and in relatives of victims of sudden arrhythmic death syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Our study is in tune with previous data that showed that ILRs are a strategic tool to guide management and reassure patients and physicians [14][15]. The increase in the use of this technology over recent years is also re ected in our data: our institution has doubled the ILR implantations during the last 5 years when compared both to previous practice and literature (Kenny et al).…”
Section: Discussionsupporting
confidence: 86%
“…Our study is in tune with previous data that showed that ILRs are a strategic tool to guide management and reassure patients and physicians [14][15]. The increase in the use of this technology over recent years is also re ected in our data: our institution has doubled the ILR implantations during the last 5 years when compared both to previous practice and literature (Kenny et al).…”
Section: Discussionsupporting
confidence: 86%
“…The present study has certain limitations that should be acknowledged. Firstly, the small sample size might have limited the precision of the estimates and the inclusion of patients with not fully established indications for ICM, such as structural heart disease or with arrhythmic inherited diseases 29 . Secondly, the retrospective design could have introduced potential inaccuracies in the data collected from medical records and resulted in a lack of detailed information on treatment decisions following arrhythmic diagnoses, potentially affecting the assessment of clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the small sample size might have limited the precision of the estimates and the inclusion of patients with not fully established indications for ICM, such as structural heart disease or with arrhythmic inherited diseases. 29 Secondly, the retrospective design could have introduced potential inaccuracies in the data collected from medical records and resulted in a lack of detailed information on treatment decisions following arrhythmic diagnoses, potentially affecting the assessment of clinical relevance. Furthermore, we did not assess a possible association of SARS-CoV-2 infection with arrhythmic findings as described in previous studies that investigated the impact of COVID-19 on arrhythmic events.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Recent guidelines acknowledge consideration of the ILR to out rule malignant arrhythmia as a cause of syncope in certain inherited arrhythmia patients at low risk of sudden cardiac death. 76 …”
Section: Diagnostic Workup For Syncope Aetiology: Summary Of 25 Years...mentioning
confidence: 99%